Research on the causes and effects of marriage and annulment of marriage in the light of Qur’an and Ahadith - Qayyum Bibi (Al-Mahdi Research Journal (MRJ), 2023)
Marriage is the name of a lifelong bond and the lawful spiritual path of human survival. It is a relationship of love that wants to be maintained through communication instead of rules and this is usually the case but it is also true that there are various difficulties and difficulties in human life. This research paper aims to explore the causes and effects of marriage and annulment of marriage in the light of Qur’an and Ahadith. The research questions are: (1) what are the causes of marriage and annulment of marriage according to Qur’an and Ahadith? (2) What are the effects of marriage and annulment of marriage according to Qur’an and Ahadith? To answer these questions, a qualitative research methodology will be used to analyze the relevant sources from the Qur’an and Ahadith. The significance of this research is to provide a better understanding of the Islamic perspective on marriage and annulment of marriage. This research will contribute to the body of knowledge by providing a comprehensive analysis of the causes and effects of marriage and annulment of marriage in the light of Qur’an and Ahadith. The conclusion of this research will be that marriage and annulment of marriage are both important aspects of a Muslim’s life, and should be taken seriously in accordance with the teachings of the Qur’an and Ahadith.